2015
DOI: 10.18335/region.v1i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and Trade: A Meta-Analysis

Abstract: Abstract. Low levels of infrastructure quality and quantity can create trade impediments through increased transport costs. Since the late 1990s, an increasing number of trade studies have taken infrastructure into account. The purpose of the present paper is to quantify the importance of infrastructure for trade by means of meta-analysis and meta-regression techniques that synthesize various studies. The type of infrastructure that we focus on is mainly public infrastructure in transportation and communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 79 publications
3
17
0
Order By: Relevance
“…The regression results moreover suggest that exports are more responsive to changes in infrastructure than imports, a finding that confirms the results of Francois and Manchin (2013). It is also in line with Celbis et al (2014), who find that the e↵ect of a country's own infrastructure is greater on its exports than on its imports. Thus, infrastructure improvements appear to induce firms to export their goods much more than they induce customers to import goods or for firms to import intermediate goods.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The regression results moreover suggest that exports are more responsive to changes in infrastructure than imports, a finding that confirms the results of Francois and Manchin (2013). It is also in line with Celbis et al (2014), who find that the e↵ect of a country's own infrastructure is greater on its exports than on its imports. Thus, infrastructure improvements appear to induce firms to export their goods much more than they induce customers to import goods or for firms to import intermediate goods.…”
Section: Discussionsupporting
confidence: 82%
“…Papers in the first category focus on trade flows that are aggregated over all transport modes, whereas papers in the second category focus on specific transport modes. A more detailed review on infrastructure trade e↵ects can, for example, be found in Celbis et al (2014) or Ferrari et al (2019). One of the seminal papers belonging to the first category is by Limao and Venables (2001), who employ a gravity equation to show that transport infrastructure increases aggregated trade flows.…”
Section: N S T I T U T Eo Ft R a N S P O R Te C O N O M I C Smünstementioning
confidence: 99%
See 1 more Smart Citation
“…The spatial concentration of such past foci of interest drives a mechanism which has two components: (i) local cultural capital creates the cultural cost of migration, and thus keeps in the locality a part of its human capital that otherwise would have been washed away by economic incentives (see Sjaastad 1962;Harris and Todaro 1970;Falck et al 2014); (ii) these past foci of development are also related to the concentration of transportation networks. The latter is partially endogenous to the current economic development level, but its significance for economic development is crucial, as new investments in transport infrastructure are costly, even if they are possible and realistic investments (see Mori and Nishikimi 2002;Celbis et al 2014). Thus, a cultural corridor unites within itself previous foci of interest which are proxies of past cultural activity and lie on past significant trade and communication roads.…”
Section: The Cultural Corridor and Its Mechanism Of Impactmentioning
confidence: 99%
“…health care), environmental amenities, tourist and recreational facilities, etc. The assessment of the impact of IC on regional development calls generally for a broad multidimensional impact model (see e.g., for a general survey and meta-analytical synthesis Celbis et al 2015).…”
Section: Infrastructural Capitalmentioning
confidence: 99%